Respuesta :
1.)
=(x-8i)(x+8i)
x^2+8ix-8ix-64i^2
x^2-64i^2
x^2-64(-1)
x^2+64
2.)
=(4x-7i)(4x+7i)
16x^2+28ix-28ix-49i^2
16x^2-49i^2
16x^2-49(-1)
16x^2+49
3.)
=(x+9i)(x+9i)
x^2+9ix+9ix+81i^2
x^2+18ix+81(-1)
x^2+18ix-81
4.)
=(x-2i)(x-2i)
x^2-2ix-2ix+4i^2
x^2-4ix+4(-1)
x^2-4ix-4
5.)
=[x+(3+5i)]^2
(x+5i+3)^2
(x+5i+3)(x+5i+3)
x^2+5ix+3x+5ix+25i^2+15i+3x+15i+9
x^2+6x+10ix+30i+25i^2+9
x^2+6x+10ix+30i+25(-1)+9
x^2+6x+10ix+30i-25+9
x^2+6x+10ix+30i-16
Hope this helps :)
Polynomial identities are used to simplify equations
- The factored expression is (x- 8i)(x + 8i)
- The factored expression is (4x- 7i)(4x + 7i)
- The product (x + 9i)^2 is x^2+18ix-81
- The product (x - 2i)^2 is x^2-4ix-4
- The product is (x+(3 + 5i))^2 is x^2 +6x + 10ix + 30i -16
(1) Factor x^2 + 64
We have:
[tex]\mathbf{x^2 + 64}[/tex]
Express 64 as 8^2
[tex]\mathbf{x^2 + 64 = x^2 + 8^2}[/tex]
Rewrite the expression as
[tex]\mathbf{x^2 + 64 = x^2 - (8i)^2}[/tex]
Apply difference of two squares
[tex]\mathbf{x^2 + 64 = (x- 8i)(x + 8i)}[/tex]
Hence, the factored expression is (x- 8i)(x + 8i)
(2) Factor 16x^2 + 49
We have:
[tex]\mathbf{16x^2 + 49}[/tex]
Express 16 as 4^2, and 49 as 7^2
[tex]\mathbf{16x^2 + 49 = (4x)^2 + 7^2}[/tex]
Rewrite the expression as
[tex]\mathbf{16x^2 + 49 = (4x)^2 - (7i)^2}[/tex]
Apply difference of two squares
[tex]\mathbf{16x^2 + 49 = (4x- 7i)(4x + 7i)}[/tex]
Hence, the factored expression is (4x- 7i)(4x + 7i)
(3) The product of (x + 9i)^2
We have:
[tex]\mathbf{(x + 9i)^2}[/tex]
Rewrite as:
[tex]\mathbf{(x + 9i)^2 = (x+9i)(x+9i)}[/tex]
Expand
[tex]\mathbf{(x + 9i)^2 = x^2+9ix+9ix+81i^2}[/tex]
Evaluate like terms
[tex]\mathbf{(x + 9i)^2 = x^2+18ix+81i^2}[/tex]
Express i^2 as -1
[tex]\mathbf{(x + 9i)^2 = x^2+18ix+81(-1)}[/tex]
Evaluate the product
[tex]\mathbf{(x + 9i)^2 = x^2+18ix-81}[/tex]
Hence, the product (x + 9i)^2 is x^2+18ix-81
(4) The product of (x - 2i)^2
We have:
[tex]\mathbf{(x - 2i)^2}[/tex]
Rewrite as:
[tex]\mathbf{(x - 2i)^2 = (x - 2i)(x - 2i)}[/tex]
Expand
[tex]\mathbf{(x - 2i)^2 = x^2-2ix-2ix+4i^2}[/tex]
Evaluate like terms
[tex]\mathbf{(x - 2i)^2 = x^2-4ix+4i^2}[/tex]
Express i^2 as -1
[tex]\mathbf{(x - 2i)^2 = x^2-4ix+4(-1)}[/tex]
Evaluate the product
[tex]\mathbf{(x - 2i)^2 = x^2-4ix-4}[/tex]
Hence, the product (x - 2i)^2 is x^2-4ix-4
(5) The product of (x+(3+5i))^2
We have
[tex]\mathbf{(x+(3 + 5i))^2}[/tex]
Rewrite as:
[tex]\mathbf{(x+(3 + 5i))^2 = (x+3 + 5i)(x+ 3 + 5i)}[/tex]
Expand
[tex]\mathbf{(x+(3 + 5i))^2 = x(x+3 + 5i) +3(x+ 3 + 5i) +5i(x+ 3 + 5i)}[/tex]
[tex]\mathbf{(x+(3 + 5i))^2 = x^2 +3x + 5ix +3x+ 9 + 15i +5ix+ 15i + 25i^2}[/tex]
Collect like terms
[tex]\mathbf{(x+(3 + 5i))^2 = x^2 +3x +3x + 5ix +5ix + 15i + 15i + 25i^2+ 9}[/tex]
Express i^2 as -1
[tex]\mathbf{(x+(3 + 5i))^2 = x^2 +3x +3x + 5ix +5ix + 15i + 15i + 25(-1)+ 9}[/tex]
[tex]\mathbf{(x+(3 + 5i))^2 = x^2 +3x +3x + 5ix +5ix + 15i + 15i - 25+ 9}[/tex]
[tex]\mathbf{(x+(3 + 5i))^2 = x^2 +6x + 10ix + 30i -16}[/tex]
Hence, the product is (x+(3 + 5i))^2 is x^2 +6x + 10ix + 30i -16
Read more about polynomial identities at:
https://brainly.com/question/9514416